PENGARUH PANDANGAN, EKONOMI, DAN MINAT MAHASISWA AKUNTANSI DALAM INVESTASI SYARIAH (Studi Empiris pada Mahasiswa Akuntansi FEB Unisma) - Yoga Eka Prasetya; Abdul Wahid Mahsuni; Hariri Hariri (Universitas Islam Malang, 2022)
This study aims to determine the effect of views, economics, and interest of accounting students in sharia investment. The independent variables in this study are views, economics, and interests, while the dependent variable is sharia investment. This study uses quantitative research, because the data used are numbers. This is a primary research using a questionnaire, the respondents are Accounting students FEB UNISMA Class 2018. This study uses the Slovin formula as a data collection method. The respondents used were 169 students, the results of which were based on the Slovin formula. It can be seen that the results of this study are the view variable has no significant effect on Islamic investment (0.503 > 0.05), while the economic variable has no effect on Islamic investment (0.937 > 0.05), and the interest variable has a positive and significant effect on Islamic investment ( 0.000 < 0.05).Keywords: Outlook, Economy, Interests, Sharia Investment